2019
DOI: 10.2217/fmb-2018-0299
|View full text |Cite
|
Sign up to set email alerts
|

Candida Albicans Vaginitis in a Murine Model is Reduced by Polypeptide-Enriched Gastrodia Elata Extracts

Abstract: Aim: The primary objective of this study was to evaluate the effects of polypeptide-enriched Gastrodia elata extracts (GE) on vulvovaginal candidiasis (VVC). Materials & methods: A VVC model induced by Candida albicans ( C. albicans) infection was successfully developed in BALB/c mice. After treatment, the colony-forming unit (CFU) of vaginal lavage was measured by plating. The extent of the inflammatory response was assessed by hematoxylin-eosin (H&E) staining and enzyme-linked immunosorbent assay (EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The antimicrobial activity of GeP against fungi and gram-positive bacteria has been reported previously (19,20). our previous study demonstrated the antimicrobial activities of GeP using the agar diffusion method (20) and are now investigating the therapeutic efficacy of GEP against vulvovaginal candidiasis in mice (30). in the present study, it was demonstrated that the effects of GeP may derive from the damage caused to cell walls and membranes, triggering the leakage of genetic material and disrupting cellular metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…The antimicrobial activity of GeP against fungi and gram-positive bacteria has been reported previously (19,20). our previous study demonstrated the antimicrobial activities of GeP using the agar diffusion method (20) and are now investigating the therapeutic efficacy of GEP against vulvovaginal candidiasis in mice (30). in the present study, it was demonstrated that the effects of GeP may derive from the damage caused to cell walls and membranes, triggering the leakage of genetic material and disrupting cellular metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…As VAGINNE is derived from the fermentation broth of L. crispatus, L. gasseri, and L. jensenii, we hypothesize that the observed anti-Candida activity is, in part, attributed to the presence of bacteriocin, hydrogen peroxide, and lactic acid [22]. Due to the failure to restore healthy ora, especially Lactobacillus, regular agents used for VVC may recur or promote recurrence [23]. However, in the study, treated with VAGINNE in mice could restore Lactobacillus spp., decreasing the RVVC.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental animals were kept in Laboratory Animal Center, Xiamen University (SYXK (Min) 2018-0010). After 3 days of adaptive feeding, as previously described 4 , to induce a pseudoestrus condition, all the mice received the subcutaneous injection with 0.1 ml of estradiol valerate (0.2 mg/ml) (Sichuan Jinke Pharmaceutical Co., Ltd, Sichuan, China) every 2 days throughout the experimental period. After pseudoestrus for 6 days, 10 μl suspension of 5.0×10 6 CFU/ml of C. albicans was inoculated intravaginally continuously for 5 days ( n =24).…”
Section: Methodsmentioning
confidence: 99%